ISSR marker‐based detection of genomic stability in Cassia occidentalis L. plantlets derived from somatic embryogenesis. Issue 1 (7th October 2015) - Naz, Ruphi; Anis, Mohammad; Alatar, Abdulrahman A.
Abstract : An efficient in vitro technology has been designed for mass multiplication of Cassia occidentalis (coffee senna) through somatic embryogenesis. Genetic stability of both regenerants and mother plant was evaluated. Embryogenic calli were produced on Murashige and Skoog (MS) medium supplemented with 20.0 μM 2, 4‐dichlorophenoxy acetic acid (2, 4‐D). Induction of somatic embryos occurred after transfer of calli to medium with reduced concentration of 2, 4‐D (10.0 μM) fortified with 1.0 μM abscisic acid (ABA). Subculturing of these embryos onto the maturation medium (1.5 μM 6‐benzyladenine + 1.0 μM ABA + 0.3 μM α‐naphthalene acetic acid) favored progression of the embryos through torpedo, heart‐shaped, and cotyledonary stages; one‐half MS medium was considered the best for conversion of cotyledonary stage embryos to young plantlets. The plantlets were acclimatized to autoclaved soil rite, after which they were transferred to the green house. Among the survived plantlets, 10 plants for each primer were randomly selected for inter‐simple sequence repeat (ISSR) analysis. Of the 10 primers tested, 5 produced reproducible and monomorphic bands, 2 led to minor variation with the appearance of unique bands, and the remaining 3 did not show any banding pattern. The majority of the regenerants had similar characteristics to the donor plant, suggesting genetic homogeneity of in vitro raised plants.